Designing a graphite calorimeter for scintillator quenching measurements. (March 2020) - Christensen, Jeppe Brage; Santurio, Grichar Valdes; Vestergaard, Anne; Korreman, Stine S.; Andersen, Claus E.
Abstract: In this work, a calorimetric system based on two graphite cores for absorbed dose measurements is described. The calorimeter also serves to correct the non-proportional (quenched) response in densely ionizing beams observed in scintillators. The system is designed for high-intensity scanning proton beams, where the deposition of each spot can be monitored by a fibre-coupled plastic scintillation detector (PSD). The graphite core can be replaced by a hollow replica of the core accommodating the PSD, in principle allowing the quenched PSD response to be corrected relative to the small graphite core under nominally identical radiation conditions. This work focuses on the design of the calorimetric system to minimize the heat losses during irradiations. The operation of two graphite cores is demonstrated to be reproducible within < 1 % . Hence, the scintillator-calorimeter system is applicable for experimental scintillator quenching corrections in high-intensity ion beams where detectors as ionization chambers are insufficient. Highlights: Improved experimental ionization quenching corrections in scintillators using graphite calorimetry. Accurate μK-scale temperature measurements enable quenching-free dose measurements in graphite. The quenched response is measured with a scintillator under nominally identical radiation conditions as the graphite. A traceable correction for ionization quenching in scintillators to graphite calorimetry can be established.